Αρωματικά ελαιόλαδα - Πισσίδου, Θάλεια (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The olive tree has been known since the ancient times. The appearance and cultivation of the olive tree exist from prehistoric times. It is a tree with huge historical, economic and environmental significance, which is why it is deeply rooted in the traditional customs of each producer. It is strongly tied to environmental policy for the sustainable development of agriculture. It strengthens the multidimensional role of agriculture by offering products whose value production is measured not only in cash. Those involved in the production and marketing chain of olive products give more and more importance to the above image of the olive tree. They firmly believe that the quality of olive products may be better, with particular emphasis on the organoleptic characteristics of olive oil, colour, acidity and the oxidative stability of its fats. For the above reasons, it is explored to extend the use of olive oil to the food industry for the development of new / innovative high value-added products based on olive oil, such as aromatic olive oils, to satisfy both the consumer's needs and to obtain a comparative advantage of a product in a highly competitive environment. In the present study, the concept of aromatic olive oil is analysed and emphasis is placed mainly on the antioxidants that bear both the olive oil and the aromatic plants that have been incorporated into olive oil. Also, the effect of the addition of the aromatic plants to the quality indexes, the oxidative stability and the organoleptic properties of the olive oil are investigated.
Keywords: Olive oil; Aromatic herbs; Aromatic olive oil; Antioxidants; Ελαιόδενδρο; Ελαιόλαδο; Αρωματικά φυτά; Αρωματικό ελαιόλαδο; Αντιοξειδωτικά